The software developer's guide - Hentzen, Whil (Hentzenwerke Pub., 2002)
Annotation There are plenty of books that show you how to write applications in a specific language. They explain the nuts and bolts of the syntax and the use of the tools to build applications with the latest features and functionality available. There are also a number of fine books that show you how to be "a computer consultant." But there are a whole host of issues specific to the business of writing, delivering and supporting custom software systems. This is the only book that will take you on a step-by-step tour of the entire process. "DevGuide 3", with over 150 pages of new material, shows you how to do "The Other 90%" of the work involved in producing custom software applications